General Biology I Survey of Cellular Biology - Bartee, Lisa; Anderson, Christine (Open textbook library., 2018)
BI101: Survey of Cellular Biology is intended for one term of the introductory biology course for non-science majors taught at many two- and four-year colleges. The concepts of cellular biology, as they apply to the study of life, are introduced, including parts of a cell, metabolism, and homeostasis. This textbook incorporates the mandates found in Vision and Change and focuses on the non-content aspects of biology education that are just as important. Additionally, this book explicitly teaches the general education outcomes that we have identified as important for this class. This textbook pulls together biology content resources that are accessible for our community college non-major biology students, as well as resources to provide them with explicit instruction in the quantitative literacy, communication, and information literacy general education outcomes as they relate to the biology content they are learning. Contact the author for inquiries about quiz